2011
DOI: 10.1002/apj.474
|View full text |Cite
|
Sign up to set email alerts
|

Application of heat integration in hydrocracking process

Abstract: Pinch technology has now developed into a powerful tool for heat integration of petroleum refining processes. Each process within the refinery has its own constraints against pinch analysis. In order to overcome these constraints, many applications and their solutions have been presented, such as decomposition policy and pressure drop considerations. These studies show that pinch analysis will only be suitable within the known limitations. In traditional refineries, the hydrocracking process is considered impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…In the previous related case, authors have studied the same hydrocracking process (Chevron License) and obtained favorable energy saving results. 2 But in this case pinch analyses of the process indicate HEN is operated efficiently. Therefore, exergy analysis is applied to significantly assist in quantifying the energy losses and the recoverable energy potential to improve the heat integration efficiency.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…In the previous related case, authors have studied the same hydrocracking process (Chevron License) and obtained favorable energy saving results. 2 But in this case pinch analyses of the process indicate HEN is operated efficiently. Therefore, exergy analysis is applied to significantly assist in quantifying the energy losses and the recoverable energy potential to improve the heat integration efficiency.…”
Section: Introductionmentioning
confidence: 94%
“…In the hydrocracking process, due to high pressure of the reactor section, which results in most expensive heat exchangers than separation section (see Table 2), decomposition was applied by dividing the overall problem into two subproblems based on pressure with specific parts of reaction and fractionation section. 2…”
Section: Pinch Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Cui and Sun [13] used pinch analysis to assess opportunities for heat integration between currently separate preheating sections for crude distillation. Goodarzvand-Chegini et al [14] instead investigated retrofitting opportunities in the hydrocracking process, which is of special interest due to high pressure levels, which impose challenging constraints on operation and plant equipment. Walmsley et al [15] recently suggested a promising approach for automated energy targeting in retrofit situations, and applied it to a large-scale refinery case study.…”
Section: Introductionmentioning
confidence: 99%
“…A centrifugal pump can work as turbine by using viscous liquids in hydrocracking processes to extract residual pressure energy in the liquid discharge from a high-pressure separator. 36 In this case, the turbine will be subject to a considerable performance degradation caused by the increased viscosity, which has been looked into in Li. 37 How the viscosity of liquid distorts the cavitation performance of a pump as turbine has not been clarified so far.…”
Section: Introductionmentioning
confidence: 99%